(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
At the present stage of development of the independent Republic of Uzbekistan, special attention is paid to the problems of becoming a spiritually rich, morally developed, independent individual. Recently, in our republic, sport occupies an important place in the structure of leisure of modern schoolchildren, in particular in students in higher educational institutions. Thus, sports are one of the few activities that have retained their status in the youth subculture, despite the significant socio-cultural transformations that have occurred in the last ten years